Short timescale imaging polarimetry of geostationary satellite Thor-6: The nature of micro-glints. Issue 10 (15th November 2022) - Wiersema, Klaas; Chote, Paul; Marchant, Jonathan; Covino, Stefano; Maund, Justyn R.; Agathanggelou, Alexander; Feline, William; George, Simon; Privett, Grant; Simmons, Brooke; Steele, Iain A.
Abstract: Large constellations of orbiting communication satellites will become an important source of noise for present and future astronomical observatories. Mitigation measures rely on high quality predictive models of the position and expected brightness of these objects. Optical linear imaging polarimetry holds promise as a quantitative tool to improve our understanding of the physics of reflection of sunlight off satellite components and through which models of expected brightness can be improved. We present the first simultaneous short-timescale linear polarimetry and optical photometry observations of a geostationary satellite, using the new MOPTOP imaging polarimeter on the 2 m Liverpool Telescope. Our target, telecommunication satellite Thor-6, shows prominent short timescale glint-like features in the lightcurve, some as short as seconds. Our polarimetric observations overlap with several of these micro-glints, and have the cadence required to resolve them. We find that the polarisation lightcurve is remarkably smooth, the short time scale glints are not seen to produce strong polarimetric features in our observation. We show how short timescale polarimetry can further constrain the properties of the components responsible for these micro-glints.